The Elements in the Medieval World : Interdisciplinary Perspectives: Earth - Cesario, Marilina,; Magennis, Hugh,; Ramazzina, Elisa, (Elements, Nature, Environment ;, 2025)
The fourteen chapters of this volume reflect the centrality of the element Earth in medieval thought and life, a centrality inherited from classical antiquity, and fundamental too in Judaeo-Christian and Islamic traditions. The chapters also reflect the multifarious nature of the ways that Earth was experienced and understood in the Middle Ages. Contributors are Sophie E.D. Abrahams, Daniel Anlezark, Marilina Cesario, Catherine Clarke, James Davis, Stephen J. Davis, Virginia Iommi Echeverría, Andrew Fear, Danielle B. Joyner, Hugh Magennis, Francesco Marzella, Tom C.B. McLeish, Patrick Naeve, Bernard O'Donoghue, Alexandra Paddock, Elisa Ramazzina, Hannah E. Smithson, Sigbjørn O. Sønnesyn , Sinéad O'Sullivan, and Margaret Tedford. See Less